Evaluating Indeterminate Interferon‐γ–Release Assay Results in Patients With Chronic Inflammatory Diseases Receiving Immunosuppressive Therapy. Issue 8 (August 2015) - Calabrese, Cassandra; Overman, Robert A.; Dusetzina, Stacie B.; Hajj‐Ali, Rula A.
<x xml:space="preserve">Abstract</x> Objective To analyze the rate of indeterminate interferon‐γ–release assay (specifically the QuantiFeron‐TB Gold In‐Tube [QFT‐GIT]) testing for Mycobacterium tuberculosis in patients with chronic inflammatory disease (CID) compared with the general hospital population (GH) and a healthy reference group of hospital employees (HR), and to analyze factors associated with an indeterminate test result. Methods Adults with a QFT‐GIT result within a large regional US health system were included. We compared the likelihood of having an indeterminate test across each patient group. Among patients with CID, we estimated the effect of glucocorticoids, biologic agents, and disease‐modifying antirheumatic drug (DMARD) use on the likelihood of having an indeterminate test, controlling for age, sex, comorbidities, and prior health services use. Results Of the 55, 108 patients who met the inclusion criteria, CID made up 5.2% (n = 2, 864), GH 48.2%, and HR 46.6% of the study population. Indeterminate results were present in 5.3% of the CID group, 1.9% of the GH group, and 1.5% of the HR group. Compared with HR, patients with CID were 2.4 times as likely to have indeterminate test results (adjusted risk ratio [RR] 2.4, 95% confidence interval [95% CI] 1.9–2.9). In adjusted models restricted to patients with CID, glucocorticoid use significantly increased the likelihood of an indeterminate test (adjusted RR 1.4 [95% CI 1.02–2.0]) while DMARD use decreased this likelihood (adjusted RR 0.7 [95% CI 0.5–0.97]) when compared to patients not receiving medications. Conclusion Patients with CID were more likely to have indeterminate QFT‐GIT results when compared to HR subjects. Among patients with CID, only glucocorticoid use was associated with an increased likelihood of having an indeterminate test result.